Cheyenne - Bird, F. A. (Minneapolis, Minnesota : Checkerboard Library, 2022)
Introduces young readers to the Cheyenne people, their traditional ways of life, including social structure, homes, food, art, clothing and more, their contact with Europeans, and how the Cheyenne are keeping their culture alive today.
Homelands -- Society -- Homes -- Food -- Clothing -- Crafts -- Family -- Children -- Traditions -- War -- Contact With Europeans -- Little Wolf & Dull Knife -- The Cheyenne Today.
Includes index.
6.3
3-6
820L
Keywords: Cheyenne Indians -- Juvenile literature; Indigenous peoples -- Social life and customs -- Juvenile literature; Ethnology -- Juvenile literature; Cheyenne Indians; Indigenous peoples -- Social life and customs; Ethnology; Indians of North America -- Juvenile literature